A Topical Polemic: the Reconstruction of the Argentinian Literary System - García-romeu, José (Anales de Literatura Hispanoamericana, 2008)
In 2004, Ñ, the weekly supplement to the newspaper Clarín, published a series of polemical interviews and columns concerning the Argentinian literary model. The writers involved, among whom César Aira, Ricardo Piglia, Martín Kohan and Gonzalo Garcés distinguished themselves, argued over the definition of this model, the central figures that composed it, and the role of the market in its makeup… Our aim is to put into perspective the terms of this debate by means of a chronological study which, going back to the 1980s, can highlight both the evolutions and the permanent features of Argentine’s literary field.